MAJOR TRENDS IN THE WORLD JUDO SPORT DEVELOPMENT - N. Dimitrova (Trakia Journal of Sciences)
Judo's sporting success, as a fight between attack and defense, is largely driven by the mastery of the sporting technical means. The classic Kyu/Dan system which includes all the initial technical characteristics remained. At the same time, only a limited number of gripes are used in competitive conditions. The main aim of this study is to define the general pattern in the technical development of this sport and at the same time assessing the place of the best Judoka in the total number of judo practitioners. Therefore, it is of particular interest to discover the trends in the development of sporting technical mastery. On the basis of a large-scale statistical analysis, trends in the development, usability and effectiveness of competition techniques have been evaluated. The individual characteristics of the best competitors by weight category are also analyzed. Along with the general patterns and trends, the features of the main leading schools in world judo are also distinguished. The results obtained and their analysis can contribute to adequate development and planning initial training programs and to applying a science based approach to sports technical intelligence in elite judoka mastery.